1964
DOI: 10.1002/bjs.1800510708
|View full text |Cite
|
Sign up to set email alerts
|

Perforated gastric ulcer

Abstract: young adults with a peak incidence in the third decade, whereas anaplastic carcinomas tended to occur much later, with a peak incidence in the eighth decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Therefore, a more focused look at gastric ulcers is required. Similar findings about surgical delay leading to increased mortality in gastric perforated ulcers were found in the literature [ 2 , 16 , 26 , 33 ]. This research points to the fact that a short time to surgery is critical for patient survivability, and the present study shows that indeed patients with gastric ulcer perforations all had the shortest time to surgery values for both age groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, a more focused look at gastric ulcers is required. Similar findings about surgical delay leading to increased mortality in gastric perforated ulcers were found in the literature [ 2 , 16 , 26 , 33 ]. This research points to the fact that a short time to surgery is critical for patient survivability, and the present study shows that indeed patients with gastric ulcer perforations all had the shortest time to surgery values for both age groups.…”
Section: Discussionsupporting
confidence: 87%
“…However, in our study, perforated gastric ulcer and hemorrhagic perforated gastric ulcer patients both had significantly longer HLOS values than hemorrhagic gastric ulcer patients. Certainly, it is accepted that perforations are more deadly and have more complications than hemorrhages [ 6 , 9 , 33 ]. A separate study also found that elderly patients with perforated peptic ulcers stayed in the hospital longer than younger patients with the same condition, which is supported by our data [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides harboring a risk of malignancy, gastric ulcers that perforate often recur after closure alone. Consequently, most surgeons advocate immediate gastrectomy [1], an operation associated with a relapse rate of approximately 3% [2,3].…”
mentioning
confidence: 99%
“…Hence replacement of this sequestered fluid by plasma expanders is a vital step in resuscitating the patient before operation. Provided that the operator is experienced, perforated gastric ulcers are probably best dealt with by immediate resection, as the result of simple suture are usually poor owing to overlooked carcinoma,86 reperforation, haemorrhage, and further subsequent severe ulcer symptoms, often with complications.8 7- 89 Perforation occurring in a longstanding duodenal ulcer is probably best dealt with by definitive operation, either partial gastrectomy87 88 or vagotomy and drainage.90 Those with no past history are best treated by simple suture, as follow-up series show that they have only a small chance of further symptoms over the next ten years.5'…”
Section: Perforationmentioning
confidence: 99%